HUBUNGAN ANTARA DURASI PENGASUHAN DENGAN TUMBUH KEMBANG ANAK DI TEMPAT PENITIPAN ANAK (TPA) - Lili Sofia; Oswati Hasanah; Jumaini Jumaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
The daycare center is a social welfare institution that provides substitute services for the children such as mirsery, care, and education during their parent working time. The daycare center becomes the parent’s hope for their child to get better care and parenting so that the child’s growth and development could be optimum. The aim of this study is to know the relationship between the duration of care to the child’s growth and development. This research is using correlation descriptive method with a cross sectional approach. Sampling using a cluster sampling technique with the aim of respondents were 85 people. The instruments used on this research are the filling sheet, measurement of the child’s height and weight and Denver II form to asses the child’s development. The data analysis used univariate and bivariate analysis with the spearman test. The result of the research shows that there’s no correlation between the duration of parenting to a child’s growth in daycare center ( p value 0,078 > α= 0,05), but there’s a correlation between duration of parenting to child’s development in daycare center (p value 0,037 < α= 0,05). According to the result of this study, it’s recommended for the daycare nanny to pay more attention to the child’s growth and development during the child in the daycare center, so that the child’s growth and development could be optimum based on child’s level of age. Keywords: Duration of Parenting, DayCare, Growth and Development Child’s